Pengembangan Media Pembelajaran Berbasis Assemblr Edu Untuk Meningkatkan Minat Belajar Peserta Didik SD Negeri 1 Kujon Tahun Pelajaran 2023/2024 - Galih Lintang Pinilih; Sri Suwartini; Gunawan Budi Santoso (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to develop Assemblr Edu-based learning media to enhance the learning interest of Grade IV students at SD Negeri 1 Kujon. The research falls under the category of research and development (R&D) and utilizes the ADDIE Model, involving stages of Analysis, Design, Development, Evaluation, and Implementation. Data collection was carried out using descriptive statistics, validity tests, and feasibility tests. The research results indicate that the implementation of Assemblr Edu learning media is effective in increasing students' learning interest. Data analysis shows an increase in students' learning interest after the implementation of the learning media, with an average percentage of 81%. This study is deemed highly suitable for implementation and proven effective in enhancing the learning interest of Grade IV students at SD Negeri 1 Kujon in the academic year 2023/2024.